Strengthening the Expertise of Special Assistant Teachers in the Implementation of Inclusive Education Management at the Early Childhood Education Level Based on Religion and Local Wisdom in the Badas District, Kediri Regency, East Java - Binti Su’aidah Hanur; Rismalia Sari (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
In accordance with the mandate of Law Number 20 of 2003 concerning the National Education System, Article 4 paragraph (1) education in Indonesia is carried out in a democratic and fair manner, and is not discriminatory by upholding human rights, religious values, cultural values, and national pluralism. However, the obstacle that often occurs is that inclusive education is not implemented optimally due to the lack of special educator teachers in each education unit. Community service activities based on this study program use the Participatory Action Research method where in this study researchers are directly involved in the service that is carried out. Community service based on this study program focuses on providing training to RA teachers who are prospective special educators related to facilitating children with obstacles who come to their schools. The training begins with providing initial insight into inclusive schools and the types of children with special needs, followed by screening assistance, how to analyze the results of screening, how to apply learning tailored to the obstacles found and how to provide assessments according to abilities that have not been achieved by participants educate.